Methods for Obtaining and Determination of Squalene from Natural Sources. (28th January 2015) - Popa, Ovidiu; Băbeanu, Narcisa Elena; Popa, Ioana; Niță, Sultana; Dinu-Pârvu, Cristina Elena
Abstract : Squalene is a natural dehydrotriterpenic hydrocarbon (C30 H50 ) with six double bonds, known as an intermediate in the biosynthesis of phytosterol or cholesterol in plants or animals. We have briefly reviewed the natural sources for squalene and focused on the main methods and techniques to obtain and to determine it. Some of its applications in different fields of human activity are also mentioned.